Spatiotemporal analysis of atmospheric aerosols in African environments using MERRA-2 data (1980–2024): Impacts on climate extremes - Daniel O. Omokpariola (iScience)
Summary: This study investigates atmospheric aerosol trends and their climatic impacts across Africa from 1980 to 2024 using MERRA-2 reanalysis data. It reveals rising concentrations of organic and black carbon, dust, and PM2.5, largely driven by industrialization and urbanization. These aerosols influence climate extremes by altering radiation balance and cloud dynamics, contributing to increased heatwave frequency, temperature rise, and precipitation variability. The study employs spatiotemporal analysis and predictive modeling to assess aerosol-climate interactions and their implications for human health, agriculture, and water resources. Findings highlight consistent warming, worsening drought conditions, and elevated public health risks, particularly in urban and arid regions. This work underscores the need for targeted adaptation strategies and air quality management to mitigate the socio-environmental impacts of climate change in Africa.